2020
DOI: 10.1002/esp.4808
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the LandSoil expert‐based model to map erosion and sedimentation: application to a cultivated catchment in central Belgium

Abstract: Intensive agricultural practices on sensitive soils induce high erosion rates in central Belgium. Expert-rules models quantify runoff and erosion at catchment scale, avoiding over-parameterization, and can include some direct or indirect connectivity features. The aim of this article is to test the ability of an expert-based model, LandSoil, to quantify runoff and to locate erosion and sedimentation areas in a small cultivated loamy catchment in Belgium during the years 2014, 2015 and 2016. Spatialized data ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 75 publications
(136 reference statements)
2
2
0
Order By: Relevance
“…For flow conditions below around 5 L s −1 (i.e., Q 20 % ), land structure change had no apparent adverse effect on erosion; however, with increasing flow, the contribution to sediment load increased continuously, leading to a dominant role at high flow rates. This finding is partially in line with David et al (2014) and Cantreul et al (2020). The aforementioned studies reported that landscape structure was less important for soil erosion than LUCC under normal flow conditions.…”
Section: The Dynamic Relevance Of Land Consolidation In Controlling S...supporting
confidence: 78%
See 1 more Smart Citation
“…For flow conditions below around 5 L s −1 (i.e., Q 20 % ), land structure change had no apparent adverse effect on erosion; however, with increasing flow, the contribution to sediment load increased continuously, leading to a dominant role at high flow rates. This finding is partially in line with David et al (2014) and Cantreul et al (2020). The aforementioned studies reported that landscape structure was less important for soil erosion than LUCC under normal flow conditions.…”
Section: The Dynamic Relevance Of Land Consolidation In Controlling S...supporting
confidence: 78%
“…Instead of focusing on the spatial connectivity, others (e.g., Bakker et al, 2008;Sharma et al, 2011;Chevigny et al, 2014;Wang et al, 2021;Tang et al, 2021;Madarász et al, 2021) evaluated the effect of terrain, soil properties, lithology, management practices, and other processes associated with landscape and/or land structure changes, and they highlighted their impact on sediment production. It has also been shown that the impact of landscape structure on erosion is more heterogeneous when different crops are grown, and the underlying lithology, soil properties, and topography show substantial spatial variability across the catchment (David et al, 2014;Cantreul et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Q20%), land consolidation had no apparent adverse effect on erosion control, but with increasing flow, the contribution to sediment load increased continuously, leading to a dominant role at extremely high flow rates. This finding is partially in line with David et al (2014) and Cantreul et al (2020). They reported that landscape structure was less important for soil erosion during most normal flow conditions than 495 land use and land cover.…”
Section: Parcel_effect Versus Lucc_effectsupporting
confidence: 73%
“…Bakker et al, 2008;Sharma et al, 2011;Chevigny et al, 2014;Wang et al, 2021;Tang et al, 2021;Madarász et al, 2021) evaluated the effect of terrain, soil properties, lithology, management practices and other processes associated with landscape and/or land structure changes and highlighted their impact on sediment production. It has 105 also been shown that the impact of landscape structure on erosion is more heterogeneous when different crops are grown, and the underlying lithology, soil properties and topography show substantial spatial variability across the catchment (David et al,2014;Cantreul et al, 2020). production.…”
Section: Introductionmentioning
confidence: 99%